Pattern of Bacterial Pathogens Causing Urinary Tract Infection and Their Antibiotic Sensitivity: A Tertiary Care Hospital Experience (BIRDEM Medical Journal, 2016)
Background and Aims: Urinary tract infection (UTI) is a common illness. The spectrum of bacteria causing UTI and their antibiotic sensitivity is not uniform. This study was designed to describe the bacteriological spectrum causing UTI and their antibiotic sensitivity.Methods: This cross-sectional study was done in the Department of Internal Medicine, BIRDEM General Hospital from January to June, 2013.Results: Total number of patients was 103 with females predominance (F:M ratio 2:1). Mean age was 57.5 years. Most (91.3%) of the study population were diabetic with poor glycaemic control (mean HbA1c 9.9%). Common symptoms were fever, dysuria, increased urinary frequency, suprapubic pain, vomiting and loin pain. Neutrophilic leukocytosis was common (94.2%). E. coli (79.6%) was the commonest aetiological agent followed by Klebsiella (9.7%), Citrobacter (3.9%), Acinetobacter (1.9%), Enterobacter (1.9%), Enterococcus (1.9%) and Pseudomonas (0.9%). Imipenem (100%), aminoglycosides e.g. amikacin and gentamycin and nitrofurantoin were among the most sensitive antibiotics.Conclusion: E. coli is the commonest organism causing UTI and imipenem, amikacin and nitrofurantoin are the most sensitive antibiotics.Birdem Med J 2015; 5(1): 20-23